Finance for Growth : Micro, Small, and Medium Enterprise Financing - World Bank (World Bank, Washington, DC, 2020)
This report provides an overview of the demand and supply side of MSME finance as well as certain aspects of the enabling environment. A detailed analysis of the financial sector infrastructure for MSME financing and the secured transactions framework was outside of the scope of this report but would be a useful complement. Equally useful would be a detailed analysis of bank efficiency, including competition and profitability aspects, and its effect on MSME finance.